A Thermodynamic Model for the Subsolidus Evolution and Melting of Peridotite. (4th February 2021) - Tomlinson, Emma L; Holland, Tim J B
Abstract: We present a structural update to the thermodynamic model for calculating peridotite phase relations and melt compositions at 0·01 to 60 kbar and from 600 °C to the peridotite liquidus in the system K2 O–Na2 O–CaO–FeO–MgO–Al2 O3 –SiO2 –TiO2 –Fe2 O3 –Cr2 O3  (KNCFMASTOCr), based on the model of Holland et al., 2018 [ Melting of Peridotites through to Granites: A Simple Thermodynamic Model in the System KNCFMASHTOCr. Journal of Petrology 59, 881–900 ]. The new model is better able to predict the phase relations and melting of ultramafic rocks, in particular the abundance of orthopyroxene in the residue and the concentration of silica in the melt. In addition, improvements in modelling Cr-spinels mean that the model is now able to reproduce Cr-content of garnet and spinel above and below the solidus without modification to the knorringite free energy. Model calculations indicate that, for peridotite composition KR4003, the spinel to garnet transition intersects the solidus at 22·1–24·8 kbar and orthopyroxene disappears from the solidus at 29·1 kbar. Below the solidus, the model is able to reproduce the abundances and compositions of phases in experimental studies and natural samples spanning a range of compositions, allowing it to be used for investigating subsolidus equilibration during mantle cooling and pressurisation/decompression. The liquid model provides a good fit to experimental data and is able to replicate the position of the solidus and the composition of both melt and residue at and above the solidus for a range of peridotite compositions. The model may, therefore, be used to investigate fractional mantle melting and basalt generation in modern geodynamic regimes, and also to explore equilibrium mantle melting in the early Earth. The model can also be used to explore liquid and residue compositions for melting of non-pyrolitic mantle, for which there is a paucity of experimental data. We demonstrate the scope of the model using two case studies investigating the subsolidus evolution and melting of a silica-rich cratonic peridotite from the Kaapvaal craton.